Techniques of wood carving applied in the architectural elements of Malay vernacular buildings - Nazuki, Siti Najwa; Kamaruddin, Zumahiran (2017)
This paper aims to investigate the techniques of wood carving applied in architectural elements of Malay vernacular buildings including traditional houses, mosques and palaces. The discussions are based on reviews of related researches and literatures from different sources including books, journal and conference papers. Apart from this, interviews with famous wood carvers from the east coast of Peninsular Malaysia provide detailed information on the techniques applied on wood carving elements in Malay vernacular buildings and also some observation from the site survey. In Malay vernacular buildings, the carvings are usually applied on ventilation panels of window, door and wall, railings of verandah and staircase, wall panels, leaves of door and gate, roof eaves, brackets and gable end panels. These panels are made either in the form of 3D or 2D element. The techniques used are different which include direct- piercing, semi-piercing and embossed-relief piercing. As identified from the interviews and some literature reviews, different techniques were applied in complementary with the different components of wood carving in vernacular buildings including relief carving without silat, relief carving with silat and direct piercing or fully pierced with silat. It also was found that, two types of famous form of carving used are elemental panel and 3 dimensional carving. This paper concludes that each wood carving was composed with different techniques and it is based on its fabrication for different places within the buildings. They were located to suit it functions too. Further research is recommended to investigate on the potential techniques to be sustained for modern living to ensure the sustainability of the wood carving as local heritage product.